Effectiveness of a wool based packaging system on the abundance of surface spoilage microorganisms on fresh meat - Lahme, Rabya A.; Angela, Morris; Curling, Simon; Graham., Ormondroyd.; Jones, Davey L.; Williams, Prysor A. (Al-Mukhtar Journal of Sciences, 2016)
The present study assessed the microbiological quality of meat packaged and stored at room temperature for 40 h in conventional EPS (expanded polystyrene) boxes and cardboard boxes lined with wool using standard, approved culturing techniques. Swabs were taken from a number of areas within the boxes, including the surface of the boxes (at the top, middle and bottom), within the Woolcool® felt fibres, and from condensed liquid found on the surface of meat packs. A lamb breast joint from each box was sampled directly. Plate Count Agar, violet red bile agar, malt extra agar and brilliance E. coli/coliform agar were used to assay bacteria numbers found on the different surfaces. The findings suggest that the wool may have potential market value as packaging liners for transporting meat, and possibly other food products. Further research is needed to allow better characterisation to real-world conditions, and understanding of how wool used as a packaging liner could help maintain food quality on a larger scale.